Comprehensive Physiology 2023
DOI: 10.1002/cphy.c220019
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Insulin Handling in Chronic Kidney Disease

Vishnu P. Parvathareddy,
Jiao Wu,
Sandhya S. Thomas

Abstract: Insulin regulates energy metabolism involving multiple organ systems. Insulin resistance (IR) occurs when organs exhibit reduced insulin sensitivity, leading to difficulties in maintaining glucose homeostasis. IR ensures decades prior to development of overt diabetes and can cause silent metabolic derangements. IR is typically seen very early in the course of chronic kidney disease (CKD) and is evident even when the estimated glomerular filtration rate (eGFR) is within the normal range and IR persists at vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…One of the main effects of IR is hyperinsulinemia, which impairs kidney function by increased vascular permeability, endothelial dysfunction, and glomerular hyperfiltration [ 4 ]. In a longitudinal study involving patients with CKD, individuals who exhibited IR were observed to have a greater decline in renal function compared to insulin-sensitive people [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main effects of IR is hyperinsulinemia, which impairs kidney function by increased vascular permeability, endothelial dysfunction, and glomerular hyperfiltration [ 4 ]. In a longitudinal study involving patients with CKD, individuals who exhibited IR were observed to have a greater decline in renal function compared to insulin-sensitive people [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The weakening of the effects of insulin in skeletal muscle, adipose tissue, or liver cells is known as insulin resistance (IR), which is also defined as the state of aberrant blood glucose response linked to a specific insulin concentration [ 3 ]. In patients with CKD, the etiology of tissue insensitivity to insulin is complex and includes uremic toxins, inflammatory factors, metabolic acidosis, and renin–angiotensin–aldosterone system activation [ 4 ]. Diseases such as diabetes mellitus (DM), hypertension, and metabolic syndrome (MetS) are closely related to IR and are risk factors for CKD [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation